Asynchronous Technical Interviews: Reducing the Effect of Supervised Think-Aloud on Communication Ability - Behroozi, Manhaz; Brown, Chris; Parnin, Chris (ACM Joint European Software Engineering Conference and Symposium on the Foundations of Software Engineering (ESEC/FSE), 2022)
Software engineers often face a critical test before landing a job—passing a technical interview. During these sessions, candidates must write code while thinking aloud as they work toward a solution to a problem under the watchful eye of an interviewer. While thinking aloud during technical interviews gives interviewers a picture of candidates’ problem-solving ability, surprisingly, these types of interviews often prevent candidates from communicating their thought process effectively. To understand if poor performance related to interviewer presence can be reduced while preserving communication and technical skills, we introduce asynchronous technical interviews—where candidates submit recordings of think-aloud and coding. We compare this approach to traditional whiteboard interviews and found that, by eliminating interviewer supervision, asynchronicity significantly improved the clarity of think-aloud via increased informativeness and reduced stress. Moreover, we discovered asynchronous technical interviews preserved, and in some cases even enhanced, technical problem-solving strategies and code quality. This work offers insight into asynchronous technical interviews as an design for supporting communication during interviews, and discusses trade-offs and guidelines for implementing this approach in software engineering hiring practices.